Estimated population prevalence of cardiac transthyretin amyloidosis in elderly men derived from incidental cardiac uptake from routine bone scans – "we're going to need a bigger boat". (25th November 2020) - Manning, D; Butler, T; Butler, M; Majeed, Y; Gordon, R; Qadir, G; Kazi, S; Beynon, R; Appaji, A; Patwala, A; Bailey, D; Satchithananda, D
Abstract: Background/Introduction: Transthyretin amyloidosis (TTR) is a cause of restrictive cardiomyopathy and heart failure predominantly in elderly men. Two main factors have moved TTR amyloidosis from super-specialist centres into mainstream cardiology: Non-invasive diagnosis of cardiac TTR demonstrating cardiac uptake using "bone tracers" such as diphosphono-propanodicarboxylic acid (DPD) and hydroxyethylene diphosphonate (HDP). Treatment of cardiac TTR with tafamidis. We aimed to determine the potential magnitude of referrals to our embryonic cardiac TTR service from patients having routine bone scans for non-cardiac reasons. We planned to estimate the prevalence of cardiac TTR in our local over 65 male population to plan service provision. Methods: All HDP bone scans performed at a teaching and research hospital in the UK from the 2017/18 financial year were reviewed (n=1530). Our hospital is the only provider of these scans locally. Of these, 1399 were for oncological and musculoskeletal (oncology/MSK) indications and 37 were referred to specifically "exclude amyloidosis". We excluded paediatric and duplicate follow-up imaging. There are approximately 140, 000 people over aged 65 living within our catchment region. We have assumed approximately 50% are male. Results: Myocardial uptake was present in 7/1399 of the oncology/MSK group and 3/7 (43%) of these already had features of heart failure. In these 7 patients bone scans were performed to investigate bony metastases in 6 (1 oesophageal cancer and 5 for prostate cancer) and 1 following an orthopaedic procedure. Cardiac uptake was present in 10/37 of the "exclude amyloid" group. In those with cardiac uptake across both groups (17) 94% were male with a mean age of 83 (sd ±6.59) and 41% were from the oncology/musculoskeletal group. Incidental cardiac uptake was seen in 1:200 routine HDP scans. When looking at males >65 specifically the uptake rate increases to (6 out of 701 scans) i.e. 1:117. Assuming there is no increased risk of TTR in patients with prostate or oesophageal cancer, then an estimate of cardiac TTR in the 75, 000 males over the age of 65 locally would be approximately 640 men. Conclusions: Bone scans account for 41% of all HDP scans with incidental cardiac uptake and therefore represents a significant potential referral source for a cardiac amyloid service. Our data suggests a potential prevalence of cardiac amyloidosis in 1:117 men over 65 with 43% already having heart failure symptoms and signs. Our age and sex specific prevalence suggests cardiac TTR is neither a rare nor unusual diagnosis. We will use our prevalence estimate to ensure our cardiac TTR service is resourced appropriately. We suggest that cardiac amyloid and cardio-oncology services should include pathways incorporating rapid access routes for suitable patients with incidental cardiac uptake on bone scans performed by non-cardiologists. Funding Acknowledgement: Type of funding source: None